Evaluation of Yield and Crop Water Requirement in Response to Change of Planting Date under Climate Change Conditions in Kermanshah Province - Hamed Eyni Nargeseh; Sajad Rahimi Moghaddam; Reza Deihimfard; Ali Mokhtassi-Bidgoli (Journal of Agricultural Science and Sustainable Production, 2017)
APSIM model was used to investigate yield and water requirement of maize in different planting dates under two emission scenarios (RCP4.5 and RCP8.5) at the three locations of Kermanshah province (Kermanshah, Kangavar and Eslamabad-Gharb). Climatic parameters were predicted using the AgMIP methodology. Results of this study indicated that in the future, average maize grain yield will be reduced in all locations, scenarios and planting dates (70 percent) compare to the baseline. Reasons for yield loss are increasing temperature over growing season (15.7%), decreasing length of growing season (4.7%) and is likely to concurrency time of flowering with extreme temperature. In addition, maize water requirement, on average, will be increased 14 percent is comparison to the baseline in all locations, scenarios and planting dates mainly due to rising temperature. In conventional planting date (4 May), crop water requirement of maize on average increased 12 percent under two emission scenarios compared with the baseline while on earlier and later planting dates, crop water requirement increased 15 and 7 percent, respectively. Due to the amount of higher cumulative rainfall during the growing season (54.27) on earlier planting dates (4 and 19 April) as well as lower yield loss compare to other planting dates (56 percent), earlier planting dates can be explained as adaptation strategy in order to achieve appropriate yield. The results also showed that among study locations, Eslamabad-Gharb and Kermanshah were the most suitable areas in terms of grain yield (4221.8 Kg.ha-1) and water requirement (1489.2 mm), respectively.